2020
DOI: 10.1097/md.0000000000021575
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of macrophage migration inhibitory factor expression in cancer patients

Abstract: Background: Recent studies showed that Macrophage migration inhibitory factor (MIF) is overexpressed and closely associated with prognosis in cancer patients. The present study was systematically evaluated the prognostic significance of MIF expression in cancer patients. Methods: PubMed, Cochrane library and Scopus were searched for eligible studies up to January 2020. Pooled hazard ratio with confidence interval (CI) was determined to assess the relationship between MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…MIF expression and secretion is elevated in most solid and hematogenous cancers and high MIF expression is a negative prognostic indicator in several cancer types (9). The extent of MIF expression is dependent on the tumor tissue type, stage, and grade among other factors (10). For example, intratumoral MIF is increased-versus normal tissue-three-and five-fold in endometrial carcinoma and non-small cell lung carcinoma (11,12), respectively, ten times in hepatocellular carcinoma (13) and sixty times in colorectal cancer (14).…”
Section: Mif's Mechanisms Of Actionmentioning
confidence: 99%
“…MIF expression and secretion is elevated in most solid and hematogenous cancers and high MIF expression is a negative prognostic indicator in several cancer types (9). The extent of MIF expression is dependent on the tumor tissue type, stage, and grade among other factors (10). For example, intratumoral MIF is increased-versus normal tissue-three-and five-fold in endometrial carcinoma and non-small cell lung carcinoma (11,12), respectively, ten times in hepatocellular carcinoma (13) and sixty times in colorectal cancer (14).…”
Section: Mif's Mechanisms Of Actionmentioning
confidence: 99%
“…A recent meta‐analysis revealed that MIF overexpression is associated with a poor prognosis and lower survival rates in cancer patients. Mechanistically, MIF activates the MAPK and PI3K pathways, which are crucial for regulating essential cellular functions, including cell proliferation, differentiation, apoptosis, and survival 32 . These pathways are also known to play a role in cancer development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, MIF activates the MAPK and PI3K pathways, which are crucial for regulating essential cellular functions, including cell proliferation, differentiation, apoptosis, and survival. 32 These pathways are also known to play a role in cancer development and progression. Our findings highlight the importance of MIF in CAF signalling and its potential as a prognostic factor and therapeutic target in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage migration inhibitory factor (MIF), a pivotal cytokine, is widely expressed and released by many types of cells, including macrophages, endothelial cells, and tumor cells. 2,3 It regulates a variety of cellular and biological functions, thereby contributing to the control of cell fate. 4 Mounting evidence has demonstrated the importance of MIF in cancer cells, in which the overexpressed MIF results in the manipulation of the immune system to protect cancer cells, inducing cell proliferation and angiogenesis.…”
mentioning
confidence: 99%
“…Visualization of these biomarkers is particularly important for understanding their biological roles in cellular events. Macrophage migration inhibitory factor (MIF), a pivotal cytokine, is widely expressed and released by many types of cells, including macrophages, endothelial cells, and tumor cells. , It regulates a variety of cellular and biological functions, thereby contributing to the control of cell fate . Mounting evidence has demonstrated the importance of MIF in cancer cells, in which the overexpressed MIF results in the manipulation of the immune system to protect cancer cells, inducing cell proliferation and angiogenesis. , Elevated MIF activity has also been closely connected with the metastatic potential and the alteration of tumor-suppressive pathways. , Tumor tissues, such as liver, lung, breast, colon, and brain-derived tumors, have been found to significantly overexpress MIF compared to normal cells .…”
mentioning
confidence: 99%